Pelatihan pemanfaatan flip pdf corporate edition untuk pengembangan e-modul sejarah lokal bagi MGMP Sejarah Pekanbaru - Refli Surya Barkara; Chandra Perwira Negara; Yanuar Al Fiqri; Febby Indri Rezkyana AM (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2025)
Local history is often taught through lecture-based approaches, which can result in one-way learning. Such conditions may reduce students’ engagement and opportunities to develop historical thinking skills. Technology-enhanced resources such as e-modules can make learning more interactive; however, many teachers still have limited capacity to design and implement them. This community service program provided training on developing local-history e-modules using flip pdf corporate edition. The program was conducted in three stages—preparation, implementation, and evaluation—and involved 40 history teachers from the Pekanbaru City History Teachers’ Forum (MGMP). The training also introduced basic instructional design principles for digital modules. Program effectiveness was measured using participant questionnaires covering activity satisfaction, knowledge and technology enrichment, relevance and implementation competence, facilitator and committee performance, and the suitability of training materials. The overall mean score was 3.6 on a four-point scale, indicating a very good category. These results suggest that the training successfully strengthened teachers’ readiness to develop local-history e-modules and apply them in classroom practice.